2005
DOI: 10.1536/ihj.46.373
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Nitric Oxide Level and Its Role in Slow Coronary Flow Phenomenon

Abstract: SUMMARYPrevious studies have suggested that microvascular abnormalities and endothelial dysfunction cause slow coronary flow (SCF). The objective of this study was to assess the plasma nitric oxide (NO) level and determine its role in the pathogenesis of SCF phenomenon. Thirty-six patients with SCF (group 1) and otherwise patent coronary arteries and 34 subjects with normal coronary flow (group 2) were included in the study. Coronary flow was quantified according to the TIMI Frame Count (TFC) method. Brachial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 28 publications
(35 reference statements)
3
56
2
2
Order By: Relevance
“…13) It has been demonstrated that endothelium-derived NO causes vasodilation and an increase in blood flow. The mechanisms responsible for endothelial dysfunction are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…13) It has been demonstrated that endothelium-derived NO causes vasodilation and an increase in blood flow. The mechanisms responsible for endothelial dysfunction are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…All participants completed the IIEF questionnaire. According to questions 1-5 and 15 (six questions that form the so-called 'erectile function domain' 14 ) of the questionnaire, ED severity was classified into five categories as severe (1-10), moderate (11)(12)(13)(14)(15)(16), mild to moderate (17-21), mild (22)(23)(24)(25) and no ED (26)(27)(28)(29)(30) …”
Section: Sexual Function: International Index Of Erectile Functionmentioning
confidence: 99%
“…7 Many etiological factors such as microvascular and endothelial dysfunction have been implicated. [8][9][10][11][12] Impaired endothelial function and reduced plasma level of nitric oxide in SCF have been demonstrated in some studies. [8][9][10][11][12] The aim of this present study was to investigate the degree of erectile dysfunction in patients with SCF.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with slow coronary flow, thrombolysis in myocardial infarction (TIMI) frame count 25 was higher, the plasma NO level was lower, and brachial artery endothelium-dependent flow-mediated dilatation was smaller than in subjects with normal coronary flow. 26 Endothelial dysfunction appears to contribute to the pathogenesis of slow coronary flow.…”
Section: 23mentioning
confidence: 99%